Balancing Party Control and Representative Independence in Recall Mechanisms - Kelik Endro Suryono; Sigit Handoko (Law Development Journal, 2026)
This study aims to analyze the dominance of political parties in recall mechanisms and its impact on the balance between party control and representative independence within a democratic system. The research method used is normative legal research with statutory and conceptual approaches, focusing on the analysis of constitutional provisions, legislative regulations, and relevant legal doctrines concerning recall or inter-time turnover mechanisms. The novelty of this research lies in identifying the legal gap arising from the excessive concentration of recall authority in political parties, particularly after the Constitutional Court Decision Number 008/PUU-IV/2006, which constitutionally legitimizes such authority. Unlike previous studies that primarily emphasize party discipline, this research highlights the tension between party control and the principle of popular sovereignty, as constituents are excluded from the dismissal process of their elected representatives. Based on the research, it is concluded that the current recall mechanism tends to weaken the independence of representatives and shift the center of political control from the people to party elites, thereby reducing the quality of representative democracy. Therefore, it is necessary to reform the recall mechanism by introducing more democratic, transparent, and participatory procedures to ensure a balance between party discipline, representative independence, and popular sovereignty.